Hybrid seed use and diversity of diets among women in smallholder maize-growing households in Zambia - Smale, Melinda; Moursi, Mourad; Birol, Ekin; De Groote, Hugo (International Food Policy Research Institute, 2013)
Despite the policy importance of household nutrition and food security in rural Zambia, we are not aware of any analyses since a 1994 study by Shubh Kumar that have related the adoption of hybrid seed to dietary diversity among smallholder maize growers in Zambia. We estimate regression models to test the relationship between hybrid seed use and four indicators of dietary diversity: food group diversity (24-hour), vitamin A diversity (7-day), food frequency (7-day), and frequency of consuming foods fortified with vitamin A (7-day). We find that, according to the first three indicators, women in maize-growing households that plant hybrid seed have more diverse diets. Findings are weak when we consider the frequency of consuming foods fortified with vitamin A, highlighting the importance of testing multiple indicators. Results suggest that in Zambia, families of smallholder maize farmers who do not grow hybrid seed are likely to be a disadvantaged group, with respect to maize productivity and other diet-related welfare indicators.